Gambaran VO2Max Terhadap Penderita Diabetes di Wilayah Rt 007 Rw 03 Kelurahan Ciganjur Kecamatan Jagakarsa Jakarta Selatan - Nuril Qolbiyah Al-Husna (2022)
Background : VO2Max provides many physical health benefits for people with diabetes. VO2Max is a valid parameter to evaluate good cardiorespiratory endurance and will reduce the risk of diabetes. Objective: This study aims to determine the description of VO2Max for diabetics in the area of rt 007 rw 03, ciganjur sub-district, Jagakarsa district, south jjakarta. Methods: This research is a quantitative descriptive study with a cross-sectional approach, which is a type of research in which the data will be analyzed by describing or describing the data that has been collected as it is. A total of 24 respondents participated in this study. The parameters used are a questionnaire, check the glucometer and perform the Six Minute Walking Test. In order to find out how much VO2Max is obtained for Diabetics. Results: Based on the results of data processing using SPSS 25.0, it was found that the male VO2Max risk factor obtained the most bad category with a percentage of 16.7%, the female VO2Max risk factor was in the Good category with a percentage of 37.4%. Men (29.2%), women (70.8%). And respondents (100%) had diabetes. Conclusion: The conclusion in this study is that most male diabetics have complaints of vo2max with a bad category where vo2max that occurs in diabetics has many factors that can increase complaints. In the description of VO2Max for diabetics, it can be concluded that the criteria are bad for men and good for women. Keywords: VO2Max, Diabetes